Exploring the Nexus between Environmental Degradation and Human Health in the MENAT Region: The Role of Financial Institutions’ Development - Taher, Fatma; Al-Shboul, Mohammad (International Journal of Energy Economics and Policy, 2025)
The paper examines the role played by financial institutions’ development on the nexus between environmental degradation and human health in countries in the region encompassing the Middle East, North Africa, and Turkey (MENAT). The paper argues that ecological degradation leads to better human health. However, financial institutions’ development (depth, access, and efficiency) weakens the impact of environmental degradation on human health. A comparison of oil-producing and non–oil-producing countries shows that financial institutions’ development influences the relationship between environmental degradation and human health. In oil-producing countries, enhanced financial institutions tend to significantly weaken the detrimental impact of environmental degradation on human health. However, in the non–oil-producing countries, human health tends to be weakly correlated with ecological degradation when the role of financial institutions is enhanced, confirming that financial institutions play a greater role in directing more funds to power plant projects, which enabled these countries to have less environmental degradation and stable levels of human health. These outcomes offer valuable guidance to policymakers regarding the role played by financial institutions’ development in the link between environmental degradation and human health, driving economies in the MENAT region to promote public health by adopting more effective ecofriendly programs associated with continued development of financial institutions.